Morphometry of iliotibial tract and its surgical importance: an anatomical study - Mamatha Hosapatna; Vrinda Hari Ankolekar; Aswin Das; Antony Sylvan D Souza; Anne D Souza (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2015)
Background: The fascia lata thickens over the lateral surface of thigh to form a strong band iliotibial tract. It is considered as an anterolateral knee stabilizer.Methods: The present study was carried out in 16 right and 8 left dissected lower limbs. The soft tissue was dissected and fasicalata was visualized. The ITT was defined from the iliac crest to its attachment to the tibia. Tendon of biceps femoris (BF) was identified. All the extensions of ITT were identified near its lower attachment to the tibia. The bony landmarks taken for measurements were anterior superior iliac spine (ASIS), tubercle of iliac crest (TIC), Gerdy’s tubercle on the tibia (GT), superior border of patella (SP) and most prominent point on medial malleolus (MM).Results: In the present study the length of ITT from TIC to the GT was 53.5 ±3.13cm on right side and 53.37 ±4.49cm on left side. The width of ITT at the level of superior border of patella was 2.47 ± 0.49cm on right side and 2.17 ± 0.27cm on left side. The distance of ITT from GT to BF insertion was 2.86 ± 0.49cm on right side and 2 ±.0.11cm on left side. The average extension of TFL from TIC was 16.00 ±1.29 cm and 19.5 ±3.64 on right and left sides respectively.Conclusion: The morphometry of ITT and its extensions are important not only in diagnosis of the pathologies related to it but also for a safer surgical approach.